2012
DOI: 10.1186/1471-2334-12-245
|View full text |Cite
|
Sign up to set email alerts
|

Impact of empirical treatment in extended-spectrum beta-lactamase-producing Escherichia coli and Klebsiella spp. bacteremia. A multicentric cohort study

Abstract: BackgroundThe objective of this study is to analyze the factors that are associated with the adequacy of empirical antibiotic therapy and its impact in mortality in a large cohort of patients with extended-spectrum β-lactamase (ESBL) - producing Escherichia coli and Klebsiella spp. bacteremia.MethodsCases of ESBL producing Enterobacteriaceae (ESBL-E) bacteremia collected from 2003 through 2008 in 19 hospitals in Spain. Statistical analysis was performed using multivariate logistic regression.ResultsWe analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
3
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 24 publications
4
40
3
3
Order By: Relevance
“…Clinical severity of systemic inflammatory response syndrome at the onset of infection is one of the most important predictors of mortality in Enterobacteriaceae invasive infections [Peralta et al 2012]. Therefore, providing adequate antibiotic coverage is especially important in these situations and the use of broader spectrum antibiotics or combined therapy might be justified even in the absence of individual risk factors when a multidrug-resistant organism is to be considered according to the local epidemiology.…”
Section: Clinical Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical severity of systemic inflammatory response syndrome at the onset of infection is one of the most important predictors of mortality in Enterobacteriaceae invasive infections [Peralta et al 2012]. Therefore, providing adequate antibiotic coverage is especially important in these situations and the use of broader spectrum antibiotics or combined therapy might be justified even in the absence of individual risk factors when a multidrug-resistant organism is to be considered according to the local epidemiology.…”
Section: Clinical Severitymentioning
confidence: 99%
“…Several studies demonstrated that inactive empirical therapy is independently associated with worse outcomes in patients with bacteraemia due to Enterobacteriaceae [Kang et al 2005;Peralta et al 2012;Retamar et al 2012;RodriguezBañ o et al 2010]. The fact that antimicrobial resistance to first-line agents has been increasing makes the selection of empirical therapy more difficult [Livermore et al 2008;Canton et al 2012].…”
Section: Molecular Class Enzymesmentioning
confidence: 99%
“…A recent study by Peralta et al, conducted in 19 Spanish hospitals, found that the ESBLE causing bacteremia were mainly from the urinary (55.3%) and biliary (12.7%) tracts. E. coli accounted for 89% of all ESBLE strains, and 45.7% of these were multidrug resistant (e.g., resistant to ␤-lactam-␤-lactamase inhibitor combinations, cephalosporins, quinolones, and aminoglycosides) (3). Furthermore, empirical antibiotic treatment was adequate in only 48.8% of the cases, and the in-hospital mortality was 20.9% (3).…”
mentioning
confidence: 99%
“…Wound biomaterial was the most common source of biomaterial for ESBL producing Enterobacteriaceae isolation in this study, while urine was the most commonly used biomaterial in other studies (Peralta et al, 2012;Kassakian & Mermel, 2014;Moor et al, 2008;Ruiz de Alegría et al, 2011;Kolar et al, 2006). The frequency of other biomaterial for ESBL producing bacteria detection, including abdominal cavity and abscess biomaterial, bronchoalveolar fluid, blood, and cerebrospinal fluid was approximately the same as that described in other literature sources (Peralta et al, 2012;Kassakian & Mermel, 2014;Ruiz de Alegría et al, 2011;Kolar et al, 2006;Mengistu et al, 2013). The frequency of other Enterobacteriaceae found in this study, including P. mirablis, S. marcescens, and K. oxytoca, was similar to that in other studies (Sasirekha, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This is often challenging due to high antimicrobial resistance and lack of local resistance pattern data (The New β-Lactamases -NEJM, 2015 ; Peralta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%